أبعاد المفارقة الساخرة في إبداعات شعراء الجنوب الجزائري المعاصرين "منطقة غرداية نموذجاً". (مجلة الواحات للبحوث والدراسات, 2021)
The irony has been a distinguished feature in the contemporary literary experience, It has  become a form of resistance and repudiation for the contemporary poet, using it as a means to express his reaction towards any power he faces employing various styles in particular, we mention the paradox, that  it  can, through its nearing  to reality and  the things from the point of reflecting their  inconsistency and disharmony for that it reflects  the cynical vision and intent. It  is often in targeting  criticism towards to any disharmony anomalies. And implicitly looking to retrieve the model image through access to the essence of phenomena and facts to show for its truth without falsification or distortion Leading in many cases to the induction of a new consciousness unchained from recession and follow-up     From this point of view, we seek  in this study to reveal the dimensions of paradox irony of the contemporary Algerian poet by highlighting the work of a number of Algerian  southern  poets In light of the general problem which is as follow: What are the dimensions of paradox irony in contemporary Algerian poets of southern Algeria? And is divided by a central problem of its strength: What mechanisms have these poets relied on to express the irony? This study was restricted to one area of the southern Algerian region, the study case takes the region of Ghardaia as a modelKeywords: dimensions, ironic paradox, contemporary Algerian poetry, Ghardaia.